ANALISA PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE MELALUI SERVICE QUALITY PADA PERUSAHAAN SEKTOR PERHOTELAN DI JAWA TIMUR - Joshua Novianto Lokito; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the positive and significant influence of leadership style to service quality, service quality to financial performance, and leadership style to financial performance on hospitality companies in East Java. This study used quantitative approach and the data were obtained through the distribution of questionnaires to employees and customers three-star hotel until five-star hotel in East Java. The data obtained then processed by using PLS software. The result of this study showed that there was a positive and significant relationship of leadership style to service quality, service quality to financial performance, leadership style to financial performance on hospitality companies in East Java. The direct relationship between leadership style and financial performance gave higher influence than through service quality.